Desempenho e características de carcaças de cordeiros suplementados com diferentes níveis de resíduo de biodiesel - SOARES, Bruno Cabral (2013)
Diet supplementation with biodiesel residues of confined lambs, utilizing 25 sheep, without definite breed pattern (WDB), male, castrated, with average weight of 20kg was studied. The experimental design was random blocks, with 5 repetitions per treatment and a split plot scheme toward biometrics data. The experiment lasted 70 days. The diets were composed of 34% of roughage and 61% of concentrate, based on corn, soy, mineral and 5% of oil palm kernel or biodiesel residues, in increasing percentages – zero, 25, 50, 75 and 100%. The animals were slaughtered at the end of the experiment for carcass evaluation. Significant effects (P<0.05) of percentage inclusion of residues were observed for the performance and biometrics variables demonstrated in the crescent linear effect of the regression equations, as well as for the hot carcass weight (HCW) – with an average of 14; 15.92; 16.14; 16.42 and 18.02%; and the cold carcass weight (CCW) – with an average of 13.12; 14.78; 15.06; 15.70 and 17.25% for diets, respectively, containing 0, 25, 50, 75, 100% of palm kernel biodiesel residues. The palm kernel biodiesel residue utilization in feeding growing lambs is an alternative to increase the energetic density in their diets.